Preparation of high-temperature active zirconium boride powders via precursor route and microwave sintering. (19th May 2021) - Ding, Zhihui; Huang, Xiaoli; Liu, Wulong; Kim, Ik Jin; Han, Young-Hwan
ABSTRACT: ZrB2 powders were synthesised by microwave heating using the sol–gel method for precursor with eight C6 H14 O6 (ZrOCl2 ·8H2 O), boric acid (H3 BO3 ), citric acid (I), and mannitol (as raw materials). The results show that the temperature at which the ZrB2 powder is completely synthesised by microwave heating is 1400°C, which is 300°C lower than the traditional way. XRD and SEM were used to characterise the phase composition and morphology of the powders. In addition, the effects of raw material ratios and synthesis temperature on the synthesis of powder were investigated. The effect of temperature on the purity of the synthesised zirconium boride was considerable. The nearly spherical ZrB2 ultra-fine powders of high purity were synthesised successfully at 1400°C by microwave, with the ratios of C:Zr is 7.44:1, and B:Zr is 2.77:1.